BENTUK TARI LANDOK ALUN PADA MASYARAKAT SUKU ALAS KABUPATEN ACEH TENGGARA - IRA DHIRMA FARADHISTA (Gesture: Jurnal Seni Tari, 2014)
Landok Alun dance is a traditional dance of ethnic Alas people who come from Telengat Pagan village. The existence of this dance has been threatened because of the coming culture which put the existence of this dance away slowly. This research is aimed to explain about The Form Of Landok Alun Dance In Alas Ethnic Community Southeast Aceh District. To discuss about the aim of the research, it was used the theories related to the topic of the research, such as form theory which discuss about: theme, moves of dance, floor pattern, escort, makeup, wardrobe, property and stage. Technique of collecting data was done by observation, study of literature, interviem and documentation. Data analysis in the research used qualitative descriptive. The location of the research was in Telengat Pagan village Semadam Subdistrict Southeast Aceh District. The theme of Landok Alun dance is happiness of the farmers who get new farms with good condition. Landok Alun dance is defined  as a smooth or slow dance, not only the moves space of the  dance which move not a far from one position to another. Landok Alun dance was a dance which have  no variety of floor pattern, the only floor pattern which wad formed in this dance was symmetric pattern. Escort music instrument of Landok Alun dance was richocet of rhyme which was rebounded like humming and the other escort music instrument was a music instrument which was made by holed bamboo. Makeup dancers was just natural makeup. Landok Alun dance used the peculiar clothes of Alas called Mesikhatclothes and head band called Bulang Buluh. The stage of Lnadok Alun dance is in open yard with cultivated area background. Keywords:Form, Landok Alun, Alas Ethnic